Beauveria brongniartii a potential biocontrol agent for use against manuka beetle larvae damaging dairy pastures on Cape Foulwind - Townsend, R.J.; Nelson, T.L.; Jackson, T.A. (New Zealand Plant Protection, 2010)
Manuka beetles (Pyronota sp; Scarabaeidae) are serious and persistent pests of dairy pastures on Cape Foulwind Westport When a selection of scarabactive fungal isolates were tested against 3rd instar larvae of two Pyronota species a locally sourced Beauveria brongniartii (F636) isolate consistently achieved the fastest and highest levels of larval mortality Topical application of F636 caused an average of 80 larval mortality 6 weeks posttreatment Mortality was shown to be dose rate dependent for both Pyronota species When treatments were applied by incorporating rice grains colonised by the fungus into soil simulating field application F636 again produced the fastest and highest levels of larval mortalities averaging 70 6 weeks postapplication Mortalities of both Pyronota species reached 100 after 8 weeks when the assay medium was a grey sand based soil (ex Cape Foulwind) Isolate F636 shows promise as a biological control agent for this pest and field trials have been carried out in the autumn of 2010